2019
DOI: 10.1016/j.sjbs.2019.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Mir-29b mediates the regulation of Nrf2 on airway epithelial remodeling and Th1/Th2 differentiation in COPD rats

Abstract: COPD, or Chronic obstructive pulmonary disease, is an inflammation-related disease and lead to cachexia and muscle wasting. Altered nuclear factor erythroid 2-related factor 2 (Nrf2) expression is found in patients of COPD because it is involved in pulmonary protective effects. MiR-29b could be activated by Nrf2. We hypothesized that miR-29b might mediate the regulation of Nrf2 on Th1/Th2 differentiation and airway epithelial remodeling in COPD rats. SD rats were exposed to smoke for COPD induction. Expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Mitogen-activated protein kinase (MAPK) (Liu et al , 2019a, Ola-Davies et al , 2019 and mammalian target of rapamycin (mTOR) (Qiao et al , 2019, Yuan et al , 2019 can act as upstream mediators of the Nrf2 signaling pathway. Based on these studies, we can conclude that Nrf2 pathway may be a down-stream mediator of the miRs (Chi et al , 2019, Du et al , 2019, Qin et al , 2019, Wu et al , 2019a.…”
Section: Genetic Regulationmentioning
confidence: 87%
“…Mitogen-activated protein kinase (MAPK) (Liu et al , 2019a, Ola-Davies et al , 2019 and mammalian target of rapamycin (mTOR) (Qiao et al , 2019, Yuan et al , 2019 can act as upstream mediators of the Nrf2 signaling pathway. Based on these studies, we can conclude that Nrf2 pathway may be a down-stream mediator of the miRs (Chi et al , 2019, Du et al , 2019, Qin et al , 2019, Wu et al , 2019a.…”
Section: Genetic Regulationmentioning
confidence: 87%
“…Chronic obstructive pulmonary disease (COPD) is a lung disease associated with chronic airway inflammation, which limits the airflow in the lungs. The underlying mechanisms responsible for the development of COPD involve inflammation, apoptosis, and airway epithelial remodeling [ [91] , [92] , [93] ]. It was reported that 80 % of lung cancer patients suffer from COPD [ 94 ].…”
Section: Copdmentioning
confidence: 99%
“…The experimental study found that the expression of IL-4 was significantly decreased in COPD group, which may be caused by smoke stimulation Th cell dominant differentiation (24,25). The expression of IL-4 and SIgAwas increased in Hh and Hm group, and the two closely related, so IL-4 may be one of the important factors affecting the expression of SIgA on the airway mucosal surface of rats with enhanced hydrogen.…”
Section: Discussionmentioning
confidence: 99%